Natural gas underground storage: Inventory and deliverability - Mehmet Rasin Tek
This book gives state-of-the-art methods and technology for inventory verification, delivery assurance, and salt cavity storage. It provides a comprehensive review and discussion of the current technology as well as new developments for the inventory and delivery of natural gas